2023
DOI: 10.3389/fcimb.2022.1071029
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of short-chain fatty acids in pregnancy complications

Abstract: ObjectiveTo investigate the expression of short-chain fatty acids (SCFAs)—metabolites of intestinal flora—in gestational complications of gestational diabetes mellitus (GDM), preeclampsia (PE), and intrahepatic cholestasis of pregnancy (ICP), and its clinical significance.MethodsTargeted metabonomics was used to detect SCFAs in the serum of 28 GDM pregnant women, 28 PE pregnant women, 29 ICP pregnant women, and 27 healthy pregnant women (NP); their expression changes were observed; the correlation between SCFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In contrast to other SCFAs, this study identified a significant increase in isobutyric acid in the maternal serum of patients with ICP. Your previous research has also noted that the level of isobutyric acid in the peripheral blood circulation of pregnant women with pregnancy complications, such as pre-eclampsia and gestational diabetes, significantly increased compared with the NP group, aligning with the findings of this study[ 5 , 21 ]. This suggests that isobutyric acid plays a pivotal role in promoting the progression of pregnancy complications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to other SCFAs, this study identified a significant increase in isobutyric acid in the maternal serum of patients with ICP. Your previous research has also noted that the level of isobutyric acid in the peripheral blood circulation of pregnant women with pregnancy complications, such as pre-eclampsia and gestational diabetes, significantly increased compared with the NP group, aligning with the findings of this study[ 5 , 21 ]. This suggests that isobutyric acid plays a pivotal role in promoting the progression of pregnancy complications.…”
Section: Discussionsupporting
confidence: 91%
“…Short-chain fatty acids (SCFAs), prominent metabolites of the gut microbiota, play a pivotal role in preserving host metabolism, maintaining intestinal barrier function, fostering immune tolerance, and regulating autoimmune activity[ 4 ]. SCFAs have significant connections with various pregnancy complications[ 5 ], and some SCFAs hold potential for treating such complications[ 6 ]. However, the metabolic profile of SCFAs in patients with ICP remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many were associated with lipid metabolism, glycolysis and gluconeogenic metabolic pathways, which are important for maternal health [ 110 , 111 ]. Even without bacterial translocation, the release and transfer of soluble factors from bacteria into circulation, including short-chain fatty acids and serotonergic metabolites, have been found to be associated with gestational hypertension and diabetes [ 112 , 113 ]. Several unique bacterial genes were also detected that warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study proposed for the first time claimed that protein derived from the western diet-induced insulin resistance in mice by increasing the level of iso-butyrate [ 49 ]. Results from human study also showed an increased level of iso-butyrate in the GDM group with a small sample size ( n = 28 in the GDM group and n = 27 in the healthy pregnant women group) [ 50 ]. Similarly, our results revealed a positive relationship between iso-butyrate concentration and GDM risks.…”
Section: Discussionmentioning
confidence: 99%